Contrast radiography for the diagnosis of gastric disorders in dogs - Dileepkumar K M (Department of Veterinary Surgery & Radiology, College of Veterinary and Animal Science, 2005)
The study was carried out in twelve dogs of different breeds, age and either sex, with the history of gastric problems presented to the Veterinary Hospitals of the College of Veterinary and Animal Sciences at Mannuthy and Kokkalai. These animals were randomly divided into two groups viz., Group I and Group II, each consisting of six animals.